INDONESIA’S MIDDLE POWER DIPLOMACY: AN INTERNATIONAL RELATIONS ANALYSIS OF ITS STRATEGIC ROLE WITHIN ASEAN AND THE G20 - Sione Kakala; Luisa Fangatapu; Bambang Dwi Waluyo; Toka Tupuola (Yayasan Adra Karima Hubbi, 2025)
As a middle power in international relations, Indonesia plays a pivotal role in shaping regional and global affairs, particularly within ASEAN and the G20 frameworks. Over the past decades, Indonesia has strategically positioned itself as a key diplomatic player, balancing its national interests with broader global goals. Its diplomatic actions, especially in these multilateral forums, reflect a combination of soft power and pragmatic policies that aim to maintain stability and foster economic development in Southeast Asia. This study examines Indonesia’s middle power diplomacy, focusing on its strategic role within ASEAN and the G20. It aims to assess how Indonesia uses its diplomatic leverage to influence regional security, economic cooperation, and global governance. The research also explores the challenges and opportunities that Indonesia faces in navigating these two influential organizations. A qualitative approach is employed, utilizing content analysis of official government documents, speeches by key diplomats, and relevant academic literature. Additionally, interviews with policymakers and regional experts provide insights into Indonesia’s diplomatic strategies and objectives. The study finds that Indonesia’s middle power diplomacy is characterized by active engagement, mediation, and consensus-building, which enhances its influence within ASEAN and the G20. Indonesia’s ability to bridge gaps between major powers has solidified its role as a key regional leader. Indonesia’s diplomatic strategy in ASEAN and the G20 highlights its importance as a stabilizing force in both regional and global contexts. Its middle power approach allows Indonesia to shape discussions on global governance, economic development, and security.